2021
DOI: 10.1002/rth2.12520
|View full text |Cite
|
Sign up to set email alerts
|

Global reporting of pulmonary embolism–related deaths in the World Health Organization mortality database: Vital registration data from 123 countries

Abstract: Introduction Pulmonary embolism (PE) has not been accounted for as a cause of death contributing to cause‐specific mortality in global reports. Methods We analyzed global PE‐related mortality by focusing on the latest year available for each member state in the World Health Organization (WHO) mortality database, which provides age‐sex–specific aggregated mortality data transmitted by national authorities for each underlying cause of death. PE‐related deaths were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 47 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…Moreover, we found that the use of adequate thromboprophylaxis still markedly varied across geographic regions, ranging from 38% in Asia to 69% in North America. This may be due to several factors, including national guidelines, VTE awareness, 14 health care standards, variable VTE prevalence among regions, 2 and reimbursement system. 15 In contrast, we could not find major deviations from model to model, indicating that thromboprophylaxis was given to a similar percentage of patients irrespective of the model that had been used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, we found that the use of adequate thromboprophylaxis still markedly varied across geographic regions, ranging from 38% in Asia to 69% in North America. This may be due to several factors, including national guidelines, VTE awareness, 14 health care standards, variable VTE prevalence among regions, 2 and reimbursement system. 15 In contrast, we could not find major deviations from model to model, indicating that thromboprophylaxis was given to a similar percentage of patients irrespective of the model that had been used.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) is a leading cause of cardiovascular morbidity and mortality. 1,2 VTE impairs patient prognosis and causes patient discomfort, longer hospitalizations, and higher health care costs. [3][4][5] The majority of VTE events are hospital-associated, occurring during hospitalization or within 90 days of hospital discharge 6 :…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Awareness campaigns, especially the "World Thrombosis Day" initiated globally, brought awareness to the general community, medical professionals, and stakeholders about the burden of thrombosis and promoted wide implementation of available management policies. 6 Thrombogenesis is a critical condition that should be targeted at multiple levels since only anticoagulation seems insufficient. Agents in practice for prevention of cardiovascular events act either on the risk factors of atherosclerosis or directly on thrombosis.…”
Section: Introductionmentioning
confidence: 99%